Cytosine-fused TTF: Conducting property of single-component betainic radical and self-assembling ability of hemi-deprotonated cytosine pair. Issue 1 (22nd November 2021) - Murata, Tsuyoshi; Matsui, Shogo; Saito, Gunzi
Abstract: A new tetrathiafulvalene (TTF) electron-donor molecule fused with 2-oxo-4-amino-pyrimido (cytosine) ring was synthesized. The electrochemical measurement revealed that the deprotonation on the pyrimido-ring greatly strengthened the electron-donating ability of the TTF skeleton. The neutral betainic radical in which the cytosine and TTF skeleton were the deprotonated anion and radical cation, respectively, exhibited a high conductivity of ∼10 −3 S cm −1 as a single-component organic molecule. In the crystal structure of the salt composed of 1:1 composite of neutral and deprotonated anion formed a new self-assembling structure of cytosine, a hemi-deprotonated cytosine pair, through triple complementary hydrogen-bonds.